Radiological Mapping Of Nepalese Calvaria. - Bhattarai, Manoj (Journal of Nobel Medical College, 2013)
Introduction Skull has cranial vault and base. The cranial vault is called as calvarium which roofs the cranial cavity (brain box).Cranial vault consists of frontal, parietal and occipital bones. Total thickness of calvarial bones includes outer table, diploe and inner table. Diploe is made up of spongy bone whereas outer and inner table made up of compact bone. Objective To measure the thickness of Nepalese calvarial bones i.e. Frontal, Parietal and Occipital. Methods It is a hospital base cross-sectional study. CT records of one hundred and fifty adult people were studied. Nine various points on frontal bone, seven on parietal and six on occipital were located and their thickness were measured bilaterally with help of CT scan. Results The present study showed that Mean thickness+_SD of frontal bone were 6.1+_1.8mm; parietal 4.6+_2.2 and occipital 9.5+_3.4. The study also showed that frontal bone had 2.4+_0.8 mm thick outer table; 1.4+_0.6mm inner table and 3.5+_1.3mm diploe. Similarly parietal bone had 1.9+_0.6 mm thick outer table; 1.1+_0.4mm inner table and 0.8+_0.5mm diploe. The occipital bone had 3.5+_1.5 mm thick outer table; 2.2+_0.8mm inner table and 4.3+_1.8mm diploe. Similarly this present study also calculated the mean thickness+_SD of outer table in the calvarium as 2.7+_1.3mm and that of inner table 1.5+_0.9 mm. Thus it concluded that outer table was thicker than inner table. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 31-35 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7670